A review of research on tether-type submerged floating tunnels. (May 2023) - Xu, Wanhai; Ma, Yexuan; Liu, Guangjun; Li, Mingliu; Li, Ang; Jia, Menglei; He, Ziqi; Du, Zunfeng
Abstract: Submerged floating tunnels (SFTs) offer many advantages over bridges and immersed tunnels, and they are regarded as the most promising form of architecture for future transportation across bodies of water. However, an SFT has not been built because there are many critical technical difficulties in its design and construction. The tether-type SFT is one of the forms with the potential for transportation applications. This paper provides a review of the progress of research on tethered SFTs and discusses the critical issues and solutions involved in their design, dynamic characteristics, safety evaluation and vibration control. Although the design and the safety evaluation of SFTs can partially refer to guidelines for floating marine structures and pipes, it is essential to establish guidelines specifically for SFTs as soon as possible. The hydrodynamic and dynamic characteristics of SFTs are usually investigated based on the segmental model, which ignores longitudinal effects. To study the complete dynamic behaviour of the SFT in the longitudinal direction, it is important to establish an overall model that considers the effects of segment joints. Tests on large-scale models of SFTs under the combined effects of waves, currents and earthquakes are rare, and much is unknown about the progressive collapse and failure mechanisms of these structures. Vibration control of an SFT could be achieved by hydrodynamic methods and mechanical methods. To further improve safety, it is essential to propose an adaptive control system for the vibration control of SFTs under the combined effects of various external loads.